Comparison of tumor-associated YAP1 fusions identifies a recurrent set of functions critical for oncogenesis - Szulzewsky, Frank (Genes Dev, 2020)
YAP1 is a transcriptional coactivator and the principal effector of the Hippo signaling pathway, which is causally implicated in human cancer. Several YAP1 gene fusions have been identified in various human cancers and identifying the essential components of this family of gene fusions has significant therapeutic value. Here, we show that the YAP1 gene fusions YAP1-MAMLD1, YAP1-FAM118B, YAP1-TFE3, and YAP1-SS18 are oncogenic in mice. Using reporter assays, RNA-seq, ChIP-seq, and loss-of-function mutations, we can show that all of these YAP1 fusion proteins exert TEAD-dependent YAP activity, while some also exert activity of the C′-terminal fusion partner. The YAP activity of the different YAP1 fusions is resistant to negative Hippo pathway regulation due to constitutive nuclear localization and resistance to degradation of the YAP1 fusion proteins. Genetic disruption of the TEAD-binding domain of these oncogenic YAP1 fusions is sufficient to inhibit tumor formation in vivo, while pharmacological inhibition of the YAP1–TEAD interaction inhibits the growth of YAP1 fusion-expressing cell lines in vitro. These results highlight TEAD-dependent YAP activity found in these gene fusions as critical for oncogenesis and implicate these YAP functions as potential therapeutic targets in YAP1 fusion-positive tumors.